Bank-Lending Standards, the Cost Channel and Inflation Dynamics - Sylvia Kaufmann; Johann Scharler (Oesterreichische Nationalbank (OeNB), 2010)
If firms borrow working capital to finance production, then nominal interest rates have a direct influence on in inflation dynamics, which appears to be the case empirically. However, interest rates may only partly mirror the cost of working capital. In this paper we explore the role of bank lending standards as a potential additional cost source and evaluate their empirical importance in explaining in ation dynamics in the US and in the euro area.
Keywords: E40; E50; 330; New Keynesian Phillips Curve; Cost Channel; Bank Lending Standards; Bayesian